A simple method for predicting the lower heating value of municipal solid waste in China based on wet physical composition. (February 2015) - Lin, Xuebin; Wang, Fei; Chi, Yong; Huang, Qunxing; Yan, Jianhua
Highlights: A rapid and cost-effective prediction for the LHV of MSW was developed. The prediction equation was based on estimated LHVs of wet combustibles in MSW. The prediction performance of the equation is suitable for practical application. Abstract: A rapid and cost-effective prediction method based on wet physical composition has been developed to determine the lower heating value (LHV) of municipal solid waste (MSW) for practical applications in China. The heating values (HVs) of clean combustibles were measured in detail, and the effect of combustibles, food waste, and ash content on HV was studied to develop the model. The weighted average HV can be used to predict the MSW HV with high accuracy. Based on the moisture measurements of each major real combustible and the HV of clean solid waste, a predictive model of the LHV of real MSW was developed. To assess the prediction performance, information was collected on 103 MSW samples from 31 major cities in China from 1994 to 2012. Compared with five predictive models based on the wet physical composition from different regions in the world, the predictive result of the developed model is the most accurate. The prediction performance can be improved further if the MSW is sorted better and if more information is collected on the individual moisture contents of the waste.